2016
DOI: 10.3402/meo.v21.29448
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the choice of general medicine as a career among Japanese medical students

Abstract: BackgroundIn Japan, there is a shortage of young physicians in various specialties; the present situation of general medicine or family medicine (GM/FM) in particular is risky. The factors influencing the career choice of Japanese medical students are poorly understood. This study aims to identify factors related to choosing GM/FM as a career.MethodsThe study was designed as a cross-sectional survey. Students at one medical school in Japan filled out a questionnaire. Students were asked to state their intended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 22 publications
6
44
0
Order By: Relevance
“…Compared to students interested in pediatrics, those interested in family medicine rated a controllable lifestyle and working outside the hospital as important positive selection criteria, while high salaries were notably less important. This is similar to the results of Japanese medical students who rated work-life balance and rural practice as an important reasons for specializing in family medicine [24]. These results slso demonstrate that although there are many similarities and some overlap among the students inclined to pursue these two specialties, they are functionally separate populations.…”
Section: Discussionsupporting
confidence: 85%
“…Compared to students interested in pediatrics, those interested in family medicine rated a controllable lifestyle and working outside the hospital as important positive selection criteria, while high salaries were notably less important. This is similar to the results of Japanese medical students who rated work-life balance and rural practice as an important reasons for specializing in family medicine [24]. These results slso demonstrate that although there are many similarities and some overlap among the students inclined to pursue these two specialties, they are functionally separate populations.…”
Section: Discussionsupporting
confidence: 85%
“…In Japan, non-controllable lifestyle specialties are general medicine/family practice, special Internal medicine, surgery, pediatrics, obstetrics & gynecology, anesthesiology, emergency medicine, and orthopedic surgery, and controllable lifestyle specialties are psychiatry, dermatology, ophthalmology, otolaryngology, urology, and radiology [13, 16]. With regard to choice of a specialty, we [17] previously defined the following 6 factors based on the items that were grouped together: Factor 1: educational experience; Factor 2: job security; Factor 3: advice from others; Factor 4: work-life balance; Factor 5: technical and research specialty; and Factor 6: personal reasons. These 6 factors collectively accounted for 47.6 % of the variance in responses.…”
Section: Methodsmentioning
confidence: 99%
“…It has been observed that medical students are more likely to become general physicians after training in communities during their undergraduate and postgraduate education. 10,11 This trend may be stronger when educational settings are in rural communities because students can experience the essence of general medicine such as patient-centered medicine, interprofessional collaboration, and community-oriented primary care. 12,13 Through these experiences, medical students may get a true sense of the importance of general physicians, which may motivate them to become general physicians.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Improved training in community medical institutes could be the key to increasing the number of general physicians. It has been observed that medical students are more likely to become general physicians after training in communities during their undergraduate and postgraduate education . This trend may be stronger when educational settings are in rural communities because students can experience the essence of general medicine such as patient‐centered medicine, interprofessional collaboration, and community‐oriented primary care .…”
Section: Introductionmentioning
confidence: 99%